Still a reasonable goal: Targeting cholesterol in dialysis and advanced chronic kidney disease patients. Issue 5 (19th June 2017) - Heine, Gunnar H.; Rogacev, Kyrill S.; Weingärtner, Oliver; Marsche, Gunther
Abstract: Chronic kidney disease (CKD) patients have a high burden of cardiovascular disease. In the general population, lipid metabolism disorders, which cause the initiation and progression of atherosclerotic vascular changes, are major targets for preventive and therapeutic strategies in cardiovascular medicine. However, data from large cohort studies and from clinical trials suggest that the treatment guidelines on cardiovascular disease prevention and therapy cannot uncritically be transferred from individuals with intact renal function to CKD patients. Thus, unlike in the general population, neither plasma levels of HDL‐cholesterol, nor the key parameter of HDL‐cholesterol function—that is, cholesterol efflux capacity—predicts future cardiovascular events. Therefore, HDL‐cholesterol should presently not be considered as therapeutic target in CKD patients. In contrast, lowering of LDL‐cholesterol has been shown to reduce cardiovascular events at least among nondialysis CKD patients. The cardiovascular benefit of targeting LDL‐cholesterol among dialysis CKD patients is less evident. We strongly believe that at least some subgroups of dialysis patients may profit from such treatment, particularly those with highest baseline LDL‐cholesterol. Finally, as CKD patients have been characterized to have rather high intestinal cholesterol absorption, and relatively low hepatic cholesterol synthesis, substituting combined statin/ezetimibe treatment for statin monotherapy may be of particular benefit for nephrologic patients.